Aortic regurgitation due to syphilis: unusual case. Issue 4 (August 1987) - O'Farrell, N
Abstract : A 28 year old man developed signs and symptoms of left ventricular failure and was found to have gross aortic regurgitation. He underwent an aortic valve replacement, and histology showed changes characteristic of syphilis. Both the age of this patient and the mode of presentation were atypical of cardiovascular syphilis.